Short-time allowances in times of crisis: A survey experiment - Gesine Stephan; Matthias Dütsch; Christopher Osiander (Journal for Labour Market Research, 2023)
During the COVID-19 pandemic, many countries used short-time work schemes, i.e., subsidies for temporary working hours reductions due to production drops. In Germany, regulations on entitlements and benefits have been much more generous during the pandemic than they were in noncrisis times. This paper conducts a factorial survey experiment among the workforce to investigate which amounts of short-time benefits and which associated replacement rates were perceived as appropriate during the pandemic. We interpret our findings in the context of the deservingness theory. Our results show that the assessments are partly consistent with the legal design features in Germany. One of our key findings is that, according to respondents, the short-time allowance should decrease slightly with an increasing duration of short-time work. In Germany, however, with the onset of the pandemic, a rule was temporarily implemented that step-wise increased short-time work benefits with the duration of short-time work.
Keywords: J38; J68; 330; Short-time work; Short-time allowance; COVID-19; Deservingness theory; Factorial survey